1992
DOI: 10.1063/1.107835
|View full text |Cite
|
Sign up to set email alerts
|

Surface segregation of In atoms during molecular beam epitaxy and its influence on the energy levels in InGaAs/GaAs quantum wells

Abstract: Surface segregation of In atoms during molecular beam epitaxy (MBE) and its influence on the energy levels in InGaAs/GaAs quantum wells (QWs) were systematically studied using secondary-ion mass spectroscopy (SIMS) and photoluminescence (PL). Strong dependence of In surface segregation on the growth conditions was found; when the growth temperature was raised from 370 to 520 °C, the segregation length was observed to increase from 0.8 up to 2.9 nm, accompanied by an appreciable peak energy shift in the PL spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
313
0
12

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(346 citation statements)
references
References 7 publications
21
313
0
12
Order By: Relevance
“…The strain effect is included via deformation potential theory. 32 i>-wit>-(^> (26) We want to point out that it is generally known that the k' p method has some problems associated with it when applied to calculations involving nanostructures.…”
Section: < 19 >mentioning
confidence: 99%
See 1 more Smart Citation
“…The strain effect is included via deformation potential theory. 32 i>-wit>-(^> (26) We want to point out that it is generally known that the k' p method has some problems associated with it when applied to calculations involving nanostructures.…”
Section: < 19 >mentioning
confidence: 99%
“…26 The eight-band k-p method represents an extension of the Luttinger-Kohn formalism, which describes coupling among the light-hole, heavy-hole and split-off valence bands to second order in k, but is modified to include the linear coupling between the conduction and valence band states. This is necessary in order to correctly model conduction band non-parabolicity.…”
Section: Electronic Structure and Optical Transitionsmentioning
confidence: 99%
“…Muraki et al 70 presented a simple exchange model for InGaAs/GaAs QWs. According to this model the In ͑cation͒ concentration in the nth monolayer can be expressed in the form…”
Section: Segregation In Epitaxial Layersmentioning
confidence: 99%
“…The previous models of segregation are based on the twostate exchange 70,71,73 mechanism, where only atomic exchange among the subsurface and surface states is considered. Godbey and Ancona 75 instead proposed to extend the kinetic model to a three-layer exchange mechanism.…”
Section: ͑6͒mentioning
confidence: 99%
“…By modelling the indium segregation, the outward displacement of the segregated WL can be calculated by integration of the analytical expression derived by Davies for the outward displacement of a cleaved quantum well [24]. Several models for indium segregation have been proposed [30][31][32][33]. We use the phenomenological model of Muraki et al [31], which has been shown to describe well the indium composition x(n) of InAs WLs [28]:…”
Section: Formation Of the Wetting Layermentioning
confidence: 99%